Ensemble Learning-Based Weed Detection from a Duck’s Perspective Using an Aquatic Drone in Rice Paddies - Soma Asuka; Tetsuya Nakamura; Ikuko Shimizu; Taiichiro Ookawa; Hironori Nakajo (Applied Sciences, 2025)
Semantic segmentation using neural networks (NNs) has significant potential for weed detection in agricultural fields. However, conventional datasets captured from aerial perspectives often fail to detect weeds that are either hidden beneath crops or submerged in water. This study proposes a method for accurately detecting weed pixels through ensemble learning-based semantic segmentation, using forward-facing images captured by a camera mounted on an aquatic drone navigating between rice plants. We also present a paddy field weed image dataset constructed to train the NN models. Multiple semantic segmentation models were trained, compared, and evaluated, achieving a weed intersection over union (IoU) of 0.441, mean IoU (mIoU) of 0.706, and pixel accuracy of 0.971.